Preparation and application of zeolite immobilized hydrogel beads

By burying the zeolite in hydrogels and using hydrogels prepared by materials such as polyvinyl alcohol and sodium alginate, the mudification problem of zeolites during the removal of ammonia nitrogen in river pollution is solved, and the rapid separation of zeolite and water is achieved. Ammonia nitrogen removal reduces treatment costs.

CN116139832BActive Publication Date: 2025-01-10JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310152587.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-22
Publication Date
2025-01-10
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

In the prior art, when zeolites are used to remove ammonia nitrogen from river pollution, they are prone to mudification due to the fine particle size, which leads to difficulty in separating solid-liquid from water, long processing time and high cost.

Method used

The zeolite was embedded in the hydrogel by embedding method, and the hydrogel was prepared by polyvinyl alcohol and sodium alginate. Combined with the glutaraldehyde acetalization reaction, it formed zeolite immobilized hydrogel with mechanical strength, which solved the zeolite The separation problem from water.

Benefits of technology

The rapid separation of zeolite and water is achieved, the ammonia nitrogen removal efficiency is improved, the treatment time and cost are reduced, and the ion exchange capacity of zeolite is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116139832B_ABST
    Figure CN116139832B_ABST
Patent Text Reader

Abstract

The present invention discloses the preparation and application of a zeolite immobilized hydrogel beads, belonging to the technical field of zeolite immobilization. The preparation method of the present invention is: first prepare EDTA-2Na modified natural micron zeolite, grind and sieve, then add polyvinyl alcohol and sodium alginate, stir and mix to obtain a modified zeolite-polyvinyl alcohol / sodium alginate mixed solution, dissolve at high temperature, and add glutaraldehyde after uniform dispersion, continue to stir evenly to obtain a mixed solution containing glutaraldehyde, use a peristaltic pump to drop the mixed solution into a high-temperature calcium chloride solution, filter, and obtain immobilized particles I; finally, immerse the solidified particles I in a high-temperature acidic sodium sulfate solution and fix and wash again to obtain zeolite immobilized beads. The present invention embeds the zeolite into the hydrogel beads by an embedding method to achieve the immobilization of the zeolite. The hydrogel-shaped zeolite can prevent the mudding phenomenon after the zeolite is added, and it is easier to separate the zeolite from water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zeolite solidification, and in particular to the preparation and application of zeolite immobilized hydrogel beads. Background Art

[0002] As an important source of urban water resources, rivers play an important role in protecting urban ecology and beautifying urban landscapes. River pollution may cause a series of hazards, such as imbalance of ecosystems, reduction of drinking water sources, reduction of aquatic animals, blackening of river water and odor, etc. Severe river pollution may cause damage to human health. Among the many factors that cause river pollution, ammonia nitrogen is an important factor in pollution, so the removal of ammonia nitrogen is particularly important. Conventional ammonia nitrogen treatment methods require the addition of microorganisms or the planting of aquatic plants for removal, but these methods have the disadvantages of long treatment time and insignificant effect, and cannot control river pollution in a short period of time.

[0003] As a natural material, natural clinoptilolite is often used as an ammonia nitrogen adsorbent due to its low price and high selective adsorption of ammonia nitrogen. In practical applications, zeolite is often crushed to micron level, which increases the specific surface area of ​​zeolite and further improves its ammonia nitrogen removal rate. However, due to the fine particle size of micron zeolite, mudification often occurs when it is added to sewage and wastewater for the adsorption of ammonia nitrogen. After adsorbing ammonia nitrogen in sewage and wastewater, it is difficult to quickly settle to the bottom and achieve solid-liquid separation from water. However, the use of filtration, natural sedimentation and other technologies usually takes a lot of time to achieve solid-liquid separation, and increases the processing cost. In view of the above situation, it is urgent to develop a zeolite immobilization technology to achieve rapid separation of zeolite and water while ensuring the denitrification capacity of zeolite. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a preparation and application of zeolite immobilized hydrogel beads. The present invention embeds zeolite into hydrogel beads by an embedding method to achieve zeolite immobilization. The hydrogel bead-shaped zeolite can prevent the mudding phenomenon after the zeolite is added, and it is easier to separate the zeolite from water.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing zeolite immobilized condensed beads is as follows:

[0007] (1) adding EDTA-2Na solution to a zeolite raw material, stirring, washing, filtering until the filtrate is neutral, and drying to obtain EDTA-2Na modified zeolite;

[0008] (2) grinding and sieving the EDTA-2Na modified zeolite to obtain EDTA-2Na modified zeolite with uniform particle size;

[0009] (3) adding water to the modified micron zeolite with uniform particle size prepared in step (2) and stirring, then adding polyvinyl alcohol and sodium alginate in sequence, stirring and mixing to form a modified zeolite-polyvinyl alcohol / sodium alginate mixed solution;

[0010] (4) placing the modified zeolite-polyvinyl alcohol / sodium alginate mixed solution in an autoclave to dissolve; after cooling, transferring to a water bath, and continuously heating and stirring until the zeolite-polyvinyl alcohol / sodium alginate are mixed and dissolved and dispersed uniformly to obtain a uniformly dispersed mixed solution;

[0011] (5) adding glutaraldehyde to the uniformly dispersed mixed solution obtained in step (4) so ​​that the molar number of glutaraldehyde relative to the total monomer units of vinyl alcohol in the polyvinyl alcohol is 2.8 to 4.2 mol%, and stirring to obtain a mixed solution containing glutaraldehyde;

[0012] (6) heating the calcium chloride solution to 60-80° C. to obtain a high-temperature calcium chloride solution, and while maintaining the constant temperature, using a peristaltic pump to uniformly add the mixed solution containing glutaraldehyde obtained in step (5) to the high-temperature calcium chloride solution, filtering, and obtaining immobilized particles I;

[0013] (7) Immersing the immobilized particles I obtained in step (6) in a 10-25% acidic sodium sulfate high temperature solution for re-immobilization to obtain immobilized particles II.

[0014] (8) The obtained immobilized particles II are washed with pure water until the washing liquid is neutral, thereby obtaining zeolite immobilized hydrogel beads.

[0015] Furthermore, in step (1), the zeolite raw material is natural clinoptilolite with a particle size of 5 to 15 μm.

[0016] Furthermore, in step (1), the concentration of the EDTA-2Na solution is 0.1 to 1.2 mol / L, the mass volume ratio (g / L) of the zeolite raw material to the EDTA-2Na solution is 5 to 15:1; the stirring speed is 200 to 300 r / min, and the time is 12 to 24 h; the drying temperature is 60 to 85°C, and the time is 10 to 12 h.

[0017] Furthermore, in step (2), the particle size of the sieve used for screening is 1200-1340 mesh.

[0018] Furthermore, in step (3), the mass fraction of the modified micron zeolite in the mixed solution is 5-25%; the mass volume ratio (g / mL) of the polyvinyl alcohol to water is 6.2-8.2:100; and the mass volume ratio (g / mL) of the sodium alginate to water is 1.4-3.2:100.

[0019] Furthermore, in step (3), the average degree of polymerization of the polyvinyl alcohol is 2400-2500, the degree of alcoholysis is 98.0-99.8%, and the viscosity is 54.0-66.0 CPS.

[0020] Furthermore, in step (4), the dissolving temperature is 115-120° C., and the time is 30-60 min; the heating and stirring temperature is 60-80° C., and the time is 30-60 min.

[0021] Furthermore, in step (5), the mass concentration of the glutaraldehyde is 25-50%; in step (6), the concentration of the calcium chloride solution is 10-66 g / L; and the flow rate of the peristaltic pump is 5-10 mL / min.

[0022] Furthermore, in step (7), the acidic sodium sulfate high temperature solution is prepared by heating the acidic sodium sulfate to 60-80° C. and maintaining the constant temperature.

[0023] A zeolite immobilized condensate bead prepared by the preparation method.

[0024] An application of the zeolite immobilized condensate beads is characterized in that the zeolite immobilized condensate beads are used for wastewater treatment.

[0025] The beneficial technical effects of the present invention are:

[0026] The present invention uses hydrogel immobilized EDTA-2Na modified micron zeolite prepared by polyvinyl alcohol and sodium alginate. When used in the process of wastewater denitrification, it overcomes the problem that the particle size of EDTA-2Na modified micron zeolite itself is too small (5-15 μm) and it is easy to dissolve in cement, so the purpose of rapid solid-liquid separation of wastewater can be achieved after wastewater denitrification. 2+ The ion exchange effect of the EDTA-2Na modified micron zeolite was used to form the first layer of calcium alginate gel membrane, which was used to initially fix the EDTA-2Na modified micron zeolite inside the gel. Then, the acetalization reaction of polyvinyl alcohol and glutaraldehyde was used to form the second layer of acetalization membrane on the surface of the first layer of gel membrane, so as to fix the zeolite in the hydrogel beads and form zeolite fixed hydrogel beads with certain mechanical strength. Without changing the original ion exchange capacity of the EDTA-2Na modified micron zeolite, rapid solid-liquid separation after wastewater denitrification was achieved.

[0027] The zeolite immobilization technology of the present invention embeds and fixes the zeolite in the hydrogel beads without substantially changing the original ion exchange capacity of the micron zeolite. The micron zeolite is evenly distributed inside the hydrogel beads, and there is no aggregation of the micron zeolite resulting in a decrease in adsorption performance due to interaction between particles.

[0028] The zeolite immobilized hydrogel beads of the present invention were used to conduct adsorption experiments on homemade water distribution and actual black and smelly river water, respectively, to achieve denitrification of wastewater and rapid separation and recovery of zeolite. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a diagram showing the removal effect of ammonia nitrogen at different dosages of 5g-30g EDTA-2Na modified micron zeolite immobilized hydrogel beads prepared in an embodiment of the present invention.

[0030] Figure 2 This is a SEM image of the pure hydrogel beads prepared in the present invention.

[0031] Figure 3 This is a SEM image of 20 g of EDTA-2Na modified micron zeolite immobilized hydrogel beads prepared in the present invention.

[0032] Figure 4 FTIR characterization diagram of pure hydrogel beads prepared in the present invention and 20g EDTA-2Na modified micron zeolite immobilized hydrogel beads.

[0033] Figure 5 XRD characterization diagram of pure hydrogel beads prepared in the present invention and 20g EDTA-2Na modified micron zeolite immobilized hydrogel beads. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0035] The present invention uses polyvinyl alcohol and sodium alginate to prepare a hydrogel solution, then adds zeolite thereto, adds glutaraldehyde and mixes evenly, and then drips the mixture evenly into a calcium chloride solution. 2+ The ion exchange reaction forms calcium alginate, which firmly wraps the zeolite inside and initially forms a hydrogel structure. The initially formed hydrogel is then transferred to an acidic sodium sulfate solution, and the salting-out effect of polyvinyl alcohol is used to make the polyvinyl alcohol and glutaraldehyde undergo acetalization reaction better under acidic and high temperature conditions, making the hydrogel more elastic, and preparing zeolite immobilized hydrogel.

[0036] The scheme of the present invention is specifically described below by way of examples.

[0037] Embodiment 1:

[0038] 5g EDTA-2Na modified micron zeolite immobilized hydrogel beads, the preparation method of which comprises the following steps:

[0039] (1) adding 0.1 mol / L EDTA-2Na solution to a natural clinoptilolite raw material with a particle size of 5 to 15 μm at a mass volume ratio (g / L) of zeolite raw material to EDTA-2Na solution of 5:1, stirring at 200 r / min for 12 h, washing, filtering until the filtrate is neutral, and drying at a temperature of 60°C for 10 h to obtain EDTA-2Na modified zeolite;

[0040] (2) grinding and sieving the EDTA-2Na modified zeolite to obtain EDTA-2Na modified zeolite with uniform particle size;

[0041] (3) Dissolve 5 g of the EDTA-2Na modified micron zeolite prepared in step (2) in 100 mL of pure water and stir to disperse evenly; accurately weigh polyvinyl alcohol 124 (average degree of polymerization: 2400-2500, degree of alcoholysis: 98.0%-99.8%) to obtain a concentration of 62 g / L (i.e., the mass volume ratio of polyvinyl alcohol to pure water); then add sodium alginate to the zeolite-polyvinyl alcohol mixture to obtain a concentration of 14 g / L, continue stirring for 30 min to dissolve the sodium alginate, and obtain a modified zeolite-polyvinyl alcohol / sodium alginate mixture. (4) The zeolite-polyvinyl alcohol / sodium alginate solution is transferred to a high-pressure sterilizer and dissolved at 120°C for 30 minutes to fully dissolve the polyvinyl alcohol and sodium alginate. After cooling, the solution is transferred to a water bath and stirred and heated to 80°C again, and stirred with a glass rod for 30 minutes to restore the fluidity of the mixed solution and to uniformly dissolve the zeolite-polyvinyl alcohol / sodium alginate to obtain a uniformly dispersed mixed solution.

[0042] (5) Adding glutaraldehyde aqueous solution (concentration of 25%) to the mixed solution, so that the number of glutaraldehyde units relative to the total vinyl alcohol monomers in the polyvinyl alcohol is 3.7 mol%. Continue stirring the mixed solution to make the zeolite-polyvinyl alcohol-sodium alginate-glutaraldehyde uniformly mixed to obtain a mixed solution containing glutaraldehyde.

[0043] (6) Using a silicone tube with an inner diameter of 7.4 mm and a peristaltic pump, the mixed solution containing glutaraldehyde in step (5) is uniformly added dropwise to 500 mL of a 10 g / L high-temperature calcium chloride solution at 75°C at a rate of 5 mL / min to achieve the first step of immobilization of the hydrogel beads. The immobilized hydrogel beads will form spheres in the calcium chloride solution and settle to the bottom of the solution. The formed hydrogel beads are filtered and retained by gauze, i.e., immobilized particles I.

[0044] (7) The immobilized particles I were then transferred to 500 mL of a 10% acidic sodium sulfate high temperature solution at 60°C and kept for 30 min to achieve the second step of immobilization of the hydrogel beads, thereby obtaining immobilized particles II.

[0045] (8) The immobilized particles II were separated and then washed with pure water until the pH was neutral, thereby obtaining 5 g of EDTA-2Na modified micron zeolite immobilized hydrogel beads.

[0046] Embodiment 2:

[0047] 10g EDTA-2Na modified micron zeolite immobilized hydrogel beads, the preparation method of which comprises the following steps:

[0048] (1) adding 0.7 mol / L EDTA-2Na solution to a natural clinoptilolite raw material with a particle size of 5 to 15 μm at a mass volume ratio (g / L) of zeolite raw material to EDTA-2Na solution of 15:1, stirring at 300 r / min for 15 h, washing, filtering until the filtrate is neutral, and drying at a temperature of 85°C for 12 h to obtain EDTA-2Na modified zeolite;

[0049] (2) grinding and sieving the EDTA-2Na modified zeolite to obtain EDTA-2Na modified zeolite with uniform particle size;

[0050] (3) Dissolve 10 g of the EDTA-2Na modified micron zeolite prepared in step (2) in 100 mL of pure water and stir to disperse evenly; accurately weigh polyvinyl alcohol 124 (average degree of polymerization: 2400-2500, degree of alcoholysis: 98.0%-99.8%) to obtain a concentration of 70 g / L (i.e., the mass volume ratio of polyvinyl alcohol to pure water); then add sodium alginate to the zeolite-polyvinyl alcohol mixture to obtain a concentration of 25 g / L, continue stirring for 30 min to dissolve the sodium alginate, and obtain a modified zeolite-polyvinyl alcohol / sodium alginate mixture.

[0051] (4) The zeolite-polyvinyl alcohol-sodium alginate solution is transferred to a high-pressure sterilizer and dissolved at 115°C for 60 minutes to fully dissolve the polyvinyl alcohol and sodium alginate. After cooling, the solution is transferred to a water bath and stirred and heated to 60°C for 60 minutes to restore the fluidity of the mixed solution and to uniformly dissolve the zeolite-polyvinyl alcohol / sodium alginate to obtain a uniformly dispersed mixed solution.

[0052] (5) Adding an aqueous solution of glutaraldehyde (at a concentration of 50%) to the mixed solution, so that the number of glutaraldehyde units relative to the total vinyl alcohol monomers in the polyvinyl alcohol is 3.9 mol%, and continuing to stir the mixed solution to uniformly mix the zeolite-polyvinyl alcohol-sodium alginate-glutaraldehyde to obtain a mixed solution containing glutaraldehyde.

[0053] (6) Using a silicone tube with an inner diameter of 7.4 mm and a peristaltic pump, the mixed solution containing glutaraldehyde in step (5) is uniformly added dropwise to 500 mL of a 66 g / L high-temperature calcium chloride solution at 60°C at a rate of 10 mL / min to achieve the first step of immobilization of the hydrogel beads. The immobilized hydrogel beads will form spheres in the calcium chloride solution and settle to the bottom of the solution. The formed hydrogel beads are filtered and intercepted by gauze, i.e., immobilized particles I.

[0054] (7) Then, the particles I were transferred to 500 mL of 18% acidic sodium sulfate high temperature solution at 79°C and kept for 30 min to achieve the second step of immobilization of the hydrogel beads and obtain immobilized particles II.

[0055] (8) The immobilized particles II were separated and then washed with pure water until the pH was neutral, thereby obtaining 10 g of EDTA-2Na modified micron zeolite immobilized hydrogel beads.

[0056] Embodiment 3:

[0057] 15g EDTA-2Na modified micron zeolite immobilized hydrogel beads, the preparation method of which comprises the following steps:

[0058] (1) adding 1.2 mol / L EDTA-2Na solution to a natural clinoptilolite raw material with a particle size of 5 to 15 μm at a mass volume ratio (g / L) of zeolite raw material to EDTA-2Na solution of 10:1, stirring at 250 r / min for 18 h, washing, filtering until the filtrate is neutral, and drying at a temperature of 75°C for 11 h to obtain EDTA-2Na modified zeolite;

[0059] (2) grinding and sieving the EDTA-2Na modified zeolite to obtain EDTA-2Na modified zeolite with uniform particle size;

[0060] (3) Dissolve 15 g of the EDTA-2Na modified micron zeolite prepared in step (2) in 100 mL of pure water and stir to disperse evenly; accurately weigh polyvinyl alcohol 124 (average degree of polymerization: 2400-2500, degree of alcoholysis: 98.0%-99.8%) to obtain a concentration of 67 g / L (i.e., the mass volume ratio of polyvinyl alcohol to pure water); then add sodium alginate to the zeolite-polyvinyl alcohol mixture to obtain a concentration of 29 g / L, continue stirring for 30 min to dissolve the sodium alginate, and obtain a modified zeolite-polyvinyl alcohol / sodium alginate mixture.

[0061] (4) The zeolite-polyvinyl alcohol-sodium alginate solution is transferred to a high-pressure sterilizer and dissolved at 118°C for 45 minutes to fully dissolve the polyvinyl alcohol and sodium alginate. After cooling, the solution is transferred to a water bath and stirred and heated to 75°C for 45 minutes to restore the fluidity of the mixed solution and to uniformly dissolve the zeolite-polyvinyl alcohol / sodium alginate to obtain a uniformly dispersed mixed solution.

[0062] (5) Add glutaraldehyde aqueous solution (concentration of 35%) to the mixed solution so that the glutaraldehyde content is 4.0 mol% relative to the total monomer units of vinyl alcohol in the polyvinyl alcohol. Continue stirring the mixed solution to uniformly mix the zeolite-polyvinyl alcohol-sodium alginate-glutaraldehyde to obtain a mixed solution containing glutaraldehyde.

[0063] (6) Using a silicone tube with an inner diameter of 7.4 mm and a peristaltic pump, the mixed solution containing glutaraldehyde in step (5) is uniformly added dropwise to 500 mL of a 30 g / L high-temperature calcium chloride solution at 73°C at a rate of 5.59 mL / min to achieve the first step of immobilization of the hydrogel beads. The immobilized hydrogel beads will form spheres in the calcium chloride solution and settle to the bottom of the solution. The formed hydrogel beads are filtered and retained by gauze, i.e., immobilized particles I.

[0064] (7) Then, the particles I were transferred to 500 mL of 15.6% acidic sodium sulfate solution at 73° C. and kept for 30 min to achieve the second step of immobilization of the hydrogel beads, thereby obtaining immobilized particles II.

[0065] (8) The immobilized particles II (spherical hydrogel beads) were separated and then washed with pure water until the pH was neutral, thereby obtaining 15 g of EDTA-2Na modified micron zeolite immobilized hydrogel beads.

[0066] Embodiment 4:

[0067] 20g EDTA-2Na modified micron zeolite immobilized hydrogel beads, the preparation method of which comprises the following steps:

[0068] (1) adding 1.1 mol / L EDTA-2Na solution to a natural clinoptilolite raw material with a particle size of 5 to 15 μm at a mass volume ratio (g / L) of zeolite raw material to EDTA-2Na solution of 8:1, stirring at 230 r / min for 14 h, washing, filtering until the filtrate is neutral, and drying at a temperature of 80°C for 10.5 h to obtain EDTA-2Na modified zeolite;

[0069] (2) grinding and sieving the EDTA-2Na modified zeolite to obtain EDTA-2Na modified zeolite with uniform particle size;

[0070] (3) Dissolve 20 g of the EDTA-2Na modified micron zeolite prepared in step (2) in 100 mL of pure water and stir to disperse evenly; accurately weigh polyvinyl alcohol 124 (average degree of polymerization: 2400-2500, degree of alcoholysis: 98.0%-99.8%) to obtain a concentration of 82 g / L (i.e., the mass volume ratio of polyvinyl alcohol to pure water); then add sodium alginate to the zeolite-polyvinyl alcohol mixture to obtain a concentration of 30 g / L, continue stirring for 30 min to dissolve the sodium alginate, and obtain a modified zeolite-polyvinyl alcohol / sodium alginate mixture.

[0071] (4) The zeolite-polyvinyl alcohol-sodium alginate solution is transferred to a high-pressure sterilizer and dissolved at 116°C for 50 minutes to fully dissolve the polyvinyl alcohol and sodium alginate. After cooling, the solution is transferred to a water bath and stirred and heated to 70°C for 50 minutes to restore the fluidity of the mixed solution and to uniformly dissolve the zeolite-polyvinyl alcohol / sodium alginate to obtain a uniformly dispersed mixed solution.

[0072] (5) Adding glutaraldehyde aqueous solution (concentration of 40%) to the mixed solution, so that the number of glutaraldehyde units relative to the total vinyl alcohol monomers in the polyvinyl alcohol is 2.8 mol%. Continue stirring the mixed solution to make the zeolite-polyvinyl alcohol-sodium alginate-glutaraldehyde uniformly mixed to obtain a mixed solution containing glutaraldehyde.

[0073] (6) Using a silicone tube with an inner diameter of 7.4 mm and a peristaltic pump, the mixed solution containing glutaraldehyde in step (5) is uniformly added dropwise to 500 mL of a 60 g / L high-temperature calcium chloride solution at 71°C at a rate of 6.77 mL / min to achieve the first step of immobilization of the hydrogel beads. The immobilized hydrogel beads will form spheres in the calcium chloride solution and settle to the bottom of the solution. The formed hydrogel beads are filtered and retained by gauze, i.e., immobilized particles I.

[0074] (7) Then, the particles I were transferred to 500 mL of a 17.1% acidic sodium sulfate high temperature solution at 71°C and kept for 30 min to achieve the second step of immobilization of the hydrogel beads, thereby obtaining immobilized particles II.

[0075] (8) The immobilized particles II (spherical hydrogel beads) were separated and then washed with pure water until the pH was neutral, thereby obtaining 20 g of EDTA-2Na modified micron zeolite immobilized hydrogel beads.

[0076] Embodiment 5:

[0077] 25g EDTA-2Na modified micron zeolite immobilized hydrogel beads, the preparation method of which comprises the following steps:

[0078] (1) adding 0.6 mol / L EDTA-2Na solution to a natural clinoptilolite raw material with a particle size of 5 to 15 μm at a mass volume ratio (g / L) of zeolite raw material to EDTA-2Na solution of 7:1, stirring at 275 r / min for 24 h, washing, filtering until the filtrate is neutral, and drying at a temperature of 81°C for 11.2 h to obtain EDTA-2Na modified zeolite;

[0079] (2) grinding and sieving the EDTA-2Na modified zeolite to obtain EDTA-2Na modified zeolite with uniform particle size;

[0080] (3) Dissolve 25 g of the EDTA-2Na modified micron zeolite prepared in step (2) in 100 mL of pure water and stir to disperse evenly; accurately weigh polyvinyl alcohol 124 (average degree of polymerization: 2400-2500, degree of alcoholysis: 98.0%-99.8%) to obtain a concentration of 66 g / L (i.e., the mass volume ratio of polyvinyl alcohol to pure water); then add sodium alginate to the zeolite-polyvinyl alcohol mixture to obtain a concentration of 32 g / L, continue stirring for 30 min to dissolve the sodium alginate, and obtain a modified zeolite-polyvinyl alcohol / sodium alginate mixture.

[0081] (4) The zeolite-polyvinyl alcohol-sodium alginate solution is transferred to a high-pressure sterilizer and dissolved at 120°C for 30 minutes to fully dissolve the polyvinyl alcohol and sodium alginate. After cooling, the solution is transferred to a water bath and stirred and heated to 80°C for 55 minutes to restore the fluidity of the mixed solution and to uniformly dissolve the zeolite-polyvinyl alcohol / sodium alginate to obtain a uniformly dispersed mixed solution.

[0082] (5) Adding glutaraldehyde aqueous solution (concentration of 32%) to the mixed solution, so that the number of glutaraldehyde units relative to the total vinyl alcohol monomers in the polyvinyl alcohol is 4.2 mol%. Continue stirring the mixed solution to make the zeolite-polyvinyl alcohol-sodium alginate-glutaraldehyde uniformly mixed to obtain a mixed solution containing glutaraldehyde.

[0083] (6) Using a silicone tube with an inner diameter of 7.4 mm and a peristaltic pump, the mixed solution containing glutaraldehyde in step (5) is uniformly added dropwise to 500 mL of 66 g / L high-temperature calcium chloride solution at 80°C at a rate of 8.51 mL / min to achieve the first step of immobilization of the hydrogel beads. The immobilized hydrogel beads will form spheres in the calcium chloride solution and settle to the bottom of the solution. The formed hydrogel beads are filtered and intercepted by gauze, i.e., immobilized particles I.

[0084] (7) The hydrogel beads immobilized on particle I will then form spheres in the calcium chloride solution and settle to the bottom of the solution. The formed hydrogel beads are filtered out with gauze and then transferred to 500 mL of 25% acidic sodium sulfate solution at 80°C for 30 min to achieve the second step of immobilization of the hydrogel beads and obtain immobilized particles II.

[0085] (8) The immobilized particles II (spherical hydrogel beads) were separated and then washed with pure water until the pH was neutral, thereby obtaining 25 g of EDTA-2Na modified micron zeolite immobilized hydrogel beads.

[0086] Comparative Example 1

[0087] The method is the same as Example 4, except that steps (6) and (7) are combined, that is, steps (1) to (5) are the same as Example 4, and step (6) is to prepare a 4.9% calcium chloride solution and heat it to 71° C. to obtain a high-temperature calcium chloride solution, prepare a 17.1% acidic sodium sulfate solution and heat it to 71° C. to obtain a high-temperature calcium chloride solution, and while maintaining the constant temperature, use a silicone tube with an inner diameter of 7.4 mm and a peristaltic pump to uniformly add the mixed solution containing glutaraldehyde obtained in step (5) to a mixed solution of 500 mL of high-temperature calcium chloride and high-temperature acidic sodium sulfate solution, and keep it for 30 minutes to obtain immobilized particles.

[0088] Finally, the obtained immobilized particles are washed with pure water until the washing liquid is neutral, thereby obtaining zeolite immobilized hydrogel beads.

[0089] Comparative Example 2

[0090] The same as Example 4, the only difference is that the heating temperature of acidic sodium sulfate is 40°C.

[0091] Comparative Example 3

[0092] The same as Example 4, the only difference is that the acidic sodium sulfate is replaced by 17.1% hydrochloric acid.

[0093] Comparative Example 4

[0094] The same as Example 4, except that the concentration of the acidic sodium sulfate solution is changed to 11.36%.

[0095] Test example:

[0096] Preparation of laboratory ammonia nitrogen wastewater: simulate the preparation with tap water, take 3.819g of ammonium chloride that has been dried in an oven at 103℃ for 2h, dissolve it in water, and then dilute to 1L to obtain a 1000mg / L ammonia nitrogen stock solution. Take 20mL of the stock solution and dilute to 1L to obtain 20mg / L laboratory simulated ammonia nitrogen wastewater.

[0097] Actual black and smelly river water: Collect actual black and smelly river water, add a small amount of fermented chicken manure fertilizer, seal the container, and let it stand anaerobically for a period of time until the ammonia nitrogen concentration in the supernatant is 20 mg / L.

[0098] Ammonia nitrogen adsorption experiment: Take 0.5g, 1g, 1.5g, 2g, 2.5g, and 3g of the different materials prepared in Examples 1-5 and Comparative Examples 1 and 2, respectively, put them into a constant temperature oscillation box, set the temperature to 25°C, the adsorption time to 3h, the rotation speed to 140rpm, and then take samples to determine the ammonia nitrogen concentration.

[0099] The calculation formula of ammonia nitrogen removal rate is as follows:

[0100]

[0101] Where: Q is the ammonia nitrogen removal rate (%), C0 is the initial ammonia nitrogen concentration (mg / L), C t Ammonia nitrogen concentration under different adsorbent dosage (mg / L)

[0102] The adsorption amount is calculated as follows:

[0103]

[0104] Where: q e is the adsorption capacity of the adsorbent (mg / g); C0 is the initial concentration of ammonia nitrogen (mg / L), C t is the ammonia nitrogen concentration under different adsorbent dosages (mg / L), V is the volume of adsorbed wastewater (L), and m is the adsorbent dosage (g).

[0105] Figure 1 The removal effect diagram of different micron zeolite-loaded hydrogel beads prepared for Examples 1-5 for 100mL20mg / L ammonia nitrogen wastewater at different dosages. As can be seen from the figure, the removal rate of different zeolite-loaded hydrogel beads increases with the increase of zeolite loading under 5-20g loading conditions. This is because only zeolite works in the denitrification process, so the ammonia nitrogen removal rate of zeolite-loaded hydrogel beads under the same conditions will increase with the increase of zeolite loading. When the loading is 25g, the ammonia nitrogen removal effect will be reduced, so the loading of the present invention is preferably 20g. At the same time, it can be seen from the figure that when the dosage is 30g / L, the ammonia nitrogen removal rate tends to be stable, and the removal effect is better.

[0106] The ammonia nitrogen removal rates of the zeolites prepared in the examples of the present invention and the comparative examples at a dosage of 30 g / L are shown in Table 1.

[0107] Table 1 Ammonia nitrogen removal rate of zeolite

[0108]

[0109]

[0110] As can be seen from Table 1, the gelation step, the temperature and concentration of acidic sodium sulfate have a great influence on the ammonia nitrogen adsorption effect of the prepared hydrogel beads. If one-step gelation is performed before the shape of the hydrogel beads is formed, the shape of the prepared hydrogel beads cannot be controlled, resulting in a poor adsorption effect of the formed structure on ammonia nitrogen, so a two-step gelation method of first forming the hydrogel bead structure is selected. In addition, temperature has a great influence on the second step gelation process. Temperature will affect the intensity of the acetalization reaction between polyvinyl alcohol and glutaraldehyde. When the temperature is too low, the acetalization reaction is incomplete, resulting in insufficient mechanical strength of the hydrogel beads, affecting the subsequent adsorption of ammonia nitrogen. Sodium sulfate plays a very important role in the second step gelation process. First, polyvinyl alcohol will undergo salting out in a salt solution of a certain concentration, which will promote the acetalization reaction between polyvinyl alcohol and glutaraldehyde; secondly, sodium sulfate, as a pore-forming agent, will form very fine holes on the surface of the formed hydrogel beads, which will help to form the hydrogel beads to adsorb ammonia nitrogen.

[0111] Depend on Figure 2-3 It can be seen that there are many holes on the surface of the prepared pure hydrogel beads. When the EDTA-2Na modified micron zeolite is fixed to the hydrogel beads, it will cover these holes. The ammonia nitrogen in the wastewater will pass through these holes and exchange ions with the zeolite, thereby achieving the removal of ammonia nitrogen in the wastewater.

[0112] Depend on Figure 4-5 It can be seen that, after comparison, the 20g EDTA-2a modified micron zeolite immobilized hydrogel beads have the same functional groups and crystal structure as the pure hydrogel beads, indicating that after the EDTA-2Na modified micron zeolite is fixed on the surface of the hydrogel beads, it does not affect the structure of the hydrogel beads.

[0113] The zeolite immobilized hydrogel beads prepared by the present invention solve the problem of zeolite becoming muddy after contact with water. At the same time, the bead-shaped zeolite is easier to separate after wastewater treatment, solving the problem of long solid-liquid separation time of existing zeolite. Although its denitrification efficiency is not as high as that of zeolite powder, it is undoubtedly an advanced functional material.

[0114] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. A method for preparing zeolite immobilized condensed beads, characterized in that: The preparation method is as follows: (1) Adding EDTA-2Na solution to the zeolite raw material, stirring, washing, filtering until the filtrate is neutral, and drying to obtain EDTA-2Na modified zeolite; (2) grinding and sieving the EDTA-2Na modified zeolite to obtain EDTA-2Na modified zeolite with uniform particle size; (3) adding water to the modified micron zeolite with uniform particle size prepared in step (2) and stirring, then adding polyvinyl alcohol and sodium alginate in sequence, stirring and mixing to form a modified zeolite-polyvinyl alcohol / sodium alginate mixed solution; (4) Dissolve the modified zeolite-polyvinyl alcohol / sodium alginate mixture in an autoclave; cool it down and transfer it to a water bath, continue heating and stirring until the zeolite-polyvinyl alcohol / sodium alginate mixture is dissolved and dispersed evenly to obtain an evenly dispersed mixture; (5) adding a glutaraldehyde solution to the uniformly dispersed mixed solution obtained in step (4) so ​​that the molar percentage of glutaraldehyde relative to the total monomer units of vinyl alcohol in the polyvinyl alcohol is 2.8 to 4.2 mol %, and stirring to obtain a mixed solution containing glutaraldehyde; (6) heating the calcium chloride solution to 60-80° C. to obtain a high-temperature calcium chloride solution, and while maintaining the constant temperature, using a peristaltic pump to uniformly add the mixed solution containing glutaraldehyde obtained in step (5) to the high-temperature calcium chloride solution, and filtering to obtain immobilized particles I; (7) Immersing the immobilized particles I obtained in step (6) in a 10-25% acidic sodium sulfate high temperature solution for re-immobilization to obtain immobilized particles II. (8) The obtained immobilized particles II are washed with pure water until the washing liquid becomes neutral, thereby obtaining zeolite immobilized hydrogel beads.

2. The preparation method according to claim 1, characterized in that: In step (1), the zeolite raw material is natural clinoptilolite with a particle size of 5-15 μm.

3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the EDTA-2Na solution is 0.1-1.2 mol / L, the mass volume ratio (g / L) of the zeolite raw material to the EDTA-2Na solution is 5-15:1; the stirring speed is 200-300 r / min, and the time is 12-24 h; the drying temperature is 60-85°C, and the time is 10-12 h.

4. The preparation method according to claim 1, characterized in that: In step (3), the mass fraction of the modified micron zeolite in the mixed solution is 5-25%; the mass volume ratio (g / mL) of the polyvinyl alcohol to water is 6.2-8.2:100; and the mass volume ratio (g / mL) of the sodium alginate to water is 1.4-3.2:

100.

5. The preparation method according to claim 1, characterized in that: In step (3), the average degree of polymerization of the polyvinyl alcohol is 2400-2500, the degree of alcoholysis is 98.0-99.8%, and the viscosity is 54.0-66.0 CPS.

6. The preparation method according to claim 1, characterized in that: In step (4), the dissolving temperature is 115-120°C, and the time is 30-60 min; the heating and stirring temperature is 60-80°C, and the time is 30-60 min.

7. The preparation method according to claim 1, characterized in that: In step (5), the mass concentration of the glutaraldehyde solution is 25-50%; in step (6), the concentration of the calcium chloride solution is 10-66 g / L; and the flow rate of the peristaltic pump is 5-10 mL / min.

8. The preparation method according to claim 1, characterized in that: In step (7), the acidic sodium sulfate high temperature solution is prepared by heating the acidic sodium sulfate to 60-80° C. and maintaining the constant temperature.

9. Zeolite immobilized hydrogel beads prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the zeolite immobilized hydrogel beads according to claim 9, characterized in that: The zeolite immobilized hydrogel beads are used for wastewater treatment.

Citation Information

Patent Citations

  • METHOD FOR PREPARING A SOLUTION OF SUCROSE

    AR105789A2

  • COMBINED FILTERS.

    BE1019399A3